Comparison Between Topical Therapy And Oral Therapy In Patients With Chronic Suppurative Otitis Media - Istiana Akmal; Ahmad Ardhani Pratama; Jane Marry Caroline (Sean Institute, 2025)
suppurative otitis media (CSOM) is a middle ear infection that requires effective treatment to prevent serious complications. Treatment of CSOM involves two main methods, namely topical therapy applied directly to the area of infection to relieve local symptoms such as discharge and pain, and oral therapy that works systemically through the bloodstream to treat more extensive infections. This study uses the Literature method Review with Narrative design Review, collecting data from online sources such as Google Scholar and E- Perpusnas with the keywords